Relationships between problematic alcohol consumption and delinquent behaviour from adolescence to young adulthood. (23rd October 2015) - Miller, Peter G.; Butler, Erin; Richardson, Ben; Staiger, Petra K.; Youssef, George J.; Macdonald, Jacqui A.; Sanson, Ann; Edwards, Ben; Olsson, Craig A.
Abstract: Background: Heavy episodic drinking (HED) has been associated with increased risk for short‐ and long‐term injury and harms, such as violence and delinquent behaviour; however, the temporal relationship between the two remains unclear, particularly on transition to young adulthood. This study investigates transactional pathways between HED and delinquent behaviour from adolescence to emerging adulthood. Methods: Data were drawn from the Australian Temperament Project; a population‐based longitudinal study that has followed the health and development of participants (and parents) across 30 years from birth in 1982. The analytic sample was 1650 participants and included five measurement waves spanning adolescence (3 waves: 13–18 years) and young adulthood (2 waves; 19–24 years). Results: There was strong continuity across waves of both HED and delinquency, as well as across‐time associations between them. Delinquent behaviour in adolescence was associated with up to twofold increases in the odds of HED at each subsequent adolescent wave. HED in the late teens was associated with over fourfold increases in the odds of persistent (two waves) HED in young adulthood. HED in the late teens was associated with increases in the odds of delinquent behaviour in young adulthood (over twofold for male and one and a half‐fold for female participants). Conclusions: While delinquent behaviour predicts both future HED and future delinquent behaviour in adolescence, once young people reach the legal drinking age of 18 years, HED becomes a predictor of current and future delinquent behaviour and future HED, suggesting that increased access to alcohol increases the likelihood of young people engaging in delinquent behaviour. [Miller PG, Butler E, Richardson B, Staiger PK, Youssef GJ, Macdonald JA, Sanson A, Edwards B, Olsson CA. Relationships between problematic alcohol consumption and delinquent behaviour from adolescence to young adulthood. Drug Alcohol Rev 2016;35:317–325]